Стійкість динамічної системи з напівмарковськими перемиканнями в умовах дифузійної апроксимації - Чабанюк, Я.М. (Український математичний журнал, 2007)
Получены достаточные условия устойчивости динамической системы в полумарковской среде в условиях диффузионной аппроксимации с использованием асимптотических свойств компенсирующего оператора для полумарковского процесса, а также свойств функции Ляпунова для усредненной системы. We obtain sufficient conditions for the stability of a dynamical system in a semi-Markov medium under the conditions of diffusion approximation by using asymptotic properties of the compensation operator for a semi-Markov process and properties of the Lyapunov function for an averaged system.